2018
DOI: 10.1096/fj.201700740r
|View full text |Cite
|
Sign up to set email alerts
|

Humanized mice in studying efficacy and mechanisms of PD‐1‐targeted cancer immunotherapy

Abstract: Establishment of an in vivo small animal model of human tumor and human immune system interaction would enable preclinical investigations into the mechanisms underlying cancer immunotherapy. To this end, nonobese diabetic (NOD).Cg-PrkdcscidIL2rgtm1Wjl/Sz (null; NSG) mice were transplanted with human (h)CD34+ hematopoietic progenitor and stem cells, which leads to the development of human hematopoietic and immune systems [humanized NSG (HuNSG)]. HuNSG mice received human leukocyte antigen partially matched tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
254
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 275 publications
(278 citation statements)
references
References 51 publications
17
254
0
Order By: Relevance
“…In our hands, the MDA‐MB‐231 model exhibited a typical type I TME with high levels of TILs driving upregulation of PDL1 leading to adaptive resistance. This observation is consistent with the observed growth‐inhibitory effect of PD1 blockade in HIS mice (Wang et al ., ) and indicates that the MDA‐MB‐231 model may prove valuable for evaluating combination partners to PD1/PDL1 blockade, and possibly also treatments directed toward relieving the immune suppressive capacity of human Tregs. It is noteworthy that another group recently reported no effect on MDA‐MB‐231 PDL1 expression when transplanted subcutaneously in HIS mice (Rom‐Jurek et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In our hands, the MDA‐MB‐231 model exhibited a typical type I TME with high levels of TILs driving upregulation of PDL1 leading to adaptive resistance. This observation is consistent with the observed growth‐inhibitory effect of PD1 blockade in HIS mice (Wang et al ., ) and indicates that the MDA‐MB‐231 model may prove valuable for evaluating combination partners to PD1/PDL1 blockade, and possibly also treatments directed toward relieving the immune suppressive capacity of human Tregs. It is noteworthy that another group recently reported no effect on MDA‐MB‐231 PDL1 expression when transplanted subcutaneously in HIS mice (Rom‐Jurek et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies in HSC‐transplanted NSG mice have reported primary tumor development, but with the exception of the study by Wang et al . (), the growth pattern was either not illustrated or largely heterogeneous (Rongvaux et al ., ; Schilbach et al ., ; Wege et al ., ). The apparent cancer tolerance in BRGS‐HIS mice was not only due to an overwhelming growth rate, since the slow‐growing MDA‐MB‐468 tumors were not rejected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although PDXs have shown a good level of agreement with the course of disease evolution and treatment response observed in the tumors in the patient [30-33, 84, 85], they present some important drawbacks, such as the eventual loss of intratumoral heterogeneity [86,87] or certain engraftment bias [30,88]. Additionally, we have to consider that PDXs might not completely recapitulate the influence of the tissue of origin in tumors that have been implanted subcutaneously in immunodeficient mice and whose stroma has possibly regressed and/or been replaced by mouse stroma, altering thus their sub-clonal evolution and response to treatments [84,89]. However, our strategy can be readily adapted to derive drug-response models from continuous clinical outcome measures, such as progression free survival, which better represent the data acquired during routine clinical practice and in clinical trials.…”
Section: Resultsmentioning
confidence: 99%